Ihya Al-Mawat in the Study of Sharia Economic Interpretation and Hadith - Husaeni, Firman (Zona Law And Public Administration Indonesia, 2024)
This research discusses the concept of Ihya al-Mawat (reviving dead soil) in the perspective of interpretation and hadith of sharia economics. Ihya al-Mawat is a term in fiqh that refers to efforts to revive or utilize land that is not owned and unused. This study refers to the sharia foundation of the Qur'an, hadith, and the views of classical and contemporary jurisprudence scholars. In the Qur'an, Ihya al-Mawat is explained as part of the encouragement to take advantage of the gift of Allah SWT for the benefit of the people, as in QS. Al-Baqarah: 29. The hadiths of the Prophet PBUH support this action, by granting ownership rights to individuals who bring dead land to life as long as the land does not conflict with the rights of others. This concept is in line with the spirit of sharia to optimize natural resources to meet the economic and social needs of the community. The study also describes various Ihya al-Mawat methods, such as fertilizing the soil, planting, making fences, and digging trenches. In addition, sharia provisions and restrictions related to land that can be used as the object of Ihya al-Mawat were conveyed. This study shows the relevance of the concept of Ihya al-Mawat in the modern context as one of the solutions in overcoming the problem of abandoned land and promoting the sustainability of the sharia-based economy